Are patterns of cortical hyperexcitability altered in catamenial epilepsy?. Issue 5 (12th November 2013) - Badawy, Radwa A. B.; Vogrin, Simon J.; Lai, Alan; Cook, Mark J.
<x xml:space="preserve">Abstract</x> Objective We used transcranial magnetic stimulation to determine menstrual cycle‐related changes in cortical excitability in women with and without catamenial epilepsy and investigated whether these changes differed between ovulatory and anovulatory cohorts. Methods Healthy nonepilepsy women and women with generalized and focal epilepsy were investigated during ovulatory (n = 11, 46, and 43, respectively) and anovulatory (n = 9, 42, and 41) cycles. Patients were divided based on seizure pattern into catamenial (C1 = perimenstrual, C2 = periovulatory, C3 = luteal seizure exacerbation), noncatamenial, and seizure free. Cortical excitability was assessed using motor threshold (MT) and paired pulse stimulation at short (2–15 milliseconds) and long (100–300 milliseconds) interstimulus intervals twice, at the (1) late follicular and (2) mid luteal phases of the menstrual cycle. Results In controls, cortical excitability was greatest in the follicular study, where intracortical facilitation was increased (p < 0.05). The opposite was seen in women with epilepsy, where intracortical facilitation was greatest and intracortical inhibition was least in the luteal studies (p < 0.05). There were no differences between the ovulatory and anovulatory groups in any of the cohorts. No changes were observed in MT. Interpretation Nonhormonal factors are involved in the cyclicity of cortical excitability across the menstrual cycle. Normal menstrual cycle variations in cortical excitability are altered in a similar pattern in ovulatory and anovulatory women with epilepsy regardless of seizure patterns. The underlying neural changes associated with epilepsy may alter responses to sex hormones. This may be an important underlying mechanism for catamenial seizure clustering. Ann Neurol 2013;74:743–757